Poetic language and the problem of translating poetry - البرزنجي, دلسوز جعفر; سعيد, هاوكار عبدالرحمن (Sulaimani Journal for Humanities, 2019)
This research - on its small size - deals with an important subject, talking about the language (poetry) and different from the language of prose and language of daily communication. And it is a higher language than ordinary language, because it is the language of gesture and inspiration, and it is full of metaphors and miracles; making translation of poetry difficultBecause the translator no matter how hard he can not convey the feelings and imagination of the poet to the second recipient, because it usually deals with the form. The research speaks of the failure of grammarians and linguists in the development of fixed rules and laws of the language, because of the lack of distinction between the two languages when the extrapolation of language and rules. Thus, the research pointed to the need to pay attention to the specificity of the poetry language of linguistic critics to be aware of. And not be rigid in their dealings with the language of poets.